'Perswade us out of our selves': Margaret Cavendish's regulation of rhetoric. Issue 3 (27th May 2018) - Black, Andrew
ABSTRACT: In works like The World's Olio, Sociable Letters and Orations of a Divers Sort, Margaret Cavendish aspires to a rhetorical tradition from which she, as a woman, is excluded. However, Cavendish's aspirations are tempered by her anxiety toward rhetoric and its masculine histories, legacies and protocols, which poses a threat to Cavendish's insistent self-fashioning as "Margaret the First", an autonomous figure characterized by an eccentric defiance. Particularly in her Observations Upon Experimental Philosophy to which is Added the Description of a New Blazing World, Cavendish presents fantasies of containment and regulation, in which masculine voices are corrected and silenced by an authoritative female voice. Rooted in emerging theories of political and epistemological unification, Cavendish's gestures toward difference is tempered by a fear of political instability and a more anxious possibility that it might "perswade [her] out of [herself]". Cavendish constructs the autonomous and safeguarded space where she can best protect herself from that powerful threat of language. The symbolic exclusions and relocations of rhetoric allow Cavendish both to imagine and protect her exceptionalism.